Improving understanding in ordinary differential equations through writing in a dynamical environment - Habre, Samer (2012)
Research on writing in mathematics has shown that students learn more effectively in an environment that promotes this skill and that writing is most beneficial when it is directed at the learning aspect. Writing, however, necessitates proficiency on the part of the students that may not have been developed at earlier learning stages. Research has indicated though that the burden placed on teachers and learners to master this skill is compensated by the mathematical learning in such an environment. Techniques to successfully integrate writing in the mathematics classroom can be varied. This study is conducted on students in an introductory differential equations class in which a reformed approach is adopted be it in the topics discussed, the textbook used, the technology employed or the assignments/exams given. More precisely, the article explores the effect of writing on improving student understanding of particular topics in differential equations and investigates the development of the students’ writing skills.